2019
DOI: 10.1177/1558944719873145
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Management of Acute Osteomyelitis of the Hand: Outcomes and Cost Comparison to Standard Intravenous Regimen

Abstract: Background: Acute, direct inoculation osteomyelitis of the hand has traditionally been managed by intravenous antibiotics. With proven high levels of bone and joint penetration, specific oral antimicrobials may deliver clinical efficacy but at substantially lower cost. Methods: Sixty-nine adult patients with surgically proven acute, direct inoculation osteomyelitis of the hand were evaluated for clinical response on a 6-week postdebridement regimen of susceptibility-matched oral antibiotics. Inclusion required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Several studies have shown the effectiveness of oral antimicrobial therapy for superficial and deep infections of the hand and wrist. [13][14][15] However, it is important to recognize that proper and timely operative intervention must be performed with pharmacologic therapy to achieve source control, and that the transition to oral antibiotics should be monitored clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the effectiveness of oral antimicrobial therapy for superficial and deep infections of the hand and wrist. [13][14][15] However, it is important to recognize that proper and timely operative intervention must be performed with pharmacologic therapy to achieve source control, and that the transition to oral antibiotics should be monitored clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The oral antibiotics that have been successfully used for jaw osteomyelitis treatment include amoxicillin, amoxicillin/clavulanic acid, clindamycin, moxifloxacin, cotrimoxazole, and penicillin [17]. As for bone and joint infections in the hand, a retrospective study of 61 patients with acute inoculation osteomyelitis of the hand were treated with oral antibiotics for six months; this resulted in a 100% cure rate [11]. The antibiotics used included trimethoprim/sulfamethoxazole, levofloxacin, and moxifloxacin.…”
Section: Treatment Of Diabetic Osteomyelitismentioning
confidence: 99%
“…The selection of oral agents should be guided by bioavailability, pharmacokinetic ability to achieve adequate antibiotic concentrations at the site of infection, culture results or local antimicrobial susceptibility profiles if cultures are not available, previous antibiotic response, infection severity, and patient co-morbidities (such as renal function and allergies). Additional benefits include economic advantages [10][11][12][13], improved compliance, comparable efficacy [14,15], and favorable side effect profile [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found increasing resistance to clindamycin (from 7% to 31%) and to levofloxacin (from 12% to 56%); the risk factors for methicillin resistance were intravenous drug use, hepatitis C, and nosocomial infections for clindamycin and fever and a history of diabetes for levofloxacin. Although intravenous antibiotic administration has been considered the gold standard for the treatment of osteomyelitis, Henry and Lundy 44 demonstrated that patients with acute, direct-inoculation osteomyelitis of the hand could be successfully treated with susceptibility-matched oral antibiotics at a dramatic cost reduction ($482 compared with $21,646 per patient). Understanding poor prognosticators may be helpful in counseling patients and treating infections.…”
Section: Infectionmentioning
confidence: 99%